Réponses

2013-05-26T17:52:51+02:00

6 x + 6 = 6(x + 1) 

 

24x- 8 = 8( 3x - 1) 

 

-21x + 7 = 7  ( - 3x + 1) 

 

x + 5x² = x (1 + 5x ) 

 

6x + 6x² = 6x ( 1 + x )

 

-2x - 6x² = 2x (-1 - 3x) 

 

5(3x-1) + 3(3x - 1) = 8 (3x - 1) 

 

5 ( - 3x + 1) -9 ( - 3x + 1) =  - 4 ( 3x + 1)

 

5 ( -3x + 1 ) - ( -3x + 1) *7 =  -2 ( -3x +1)

 

-5x (- 6x - 7) + 3 (-6x -7 ) = (-6x - 7) [( -5x) +3]

 

(x+1) (x+2) - 5 (x+2) = (x+2) [(x+1) -5]

 

(x-11) (x+2)- (x-11) = (x-11) [ (x+2) -1]

 

-(x-11) (x+2) - 5x(x-11) = - (x-11) [ (x+2) - 5x ]

 

(15x+1) (13 - x) + (13-x) (3-2x) = (13 - x) [ ( 15x+1) + (3- 2x)]

 

(2x + 1)² + (2x + 1) ( x+3) = (2x + 1) [ (2x+ 1) + (x+3) ]